The Use of Discourse Markers in Written Discourse by the Students at Aviation Polytechnic of Surabaya - Lusiana Dewi Kusumayati (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2020)
Abstract. This research aims at investigating the use of DMs in expository essays written by Indonesian EFL learners with different levels of English language proficiency. 10 students from the second semester of Civil Airport Engineering Program at Politeknik Penerbangan Surabaya (Aviation Polytechnic of Surabaya) were taken as the sample. They were divided into two groups, high and low competence of writing skill. To represent the targeted DMs, it relies on Fraser’s taxonomy. The result of students’ writing indicates that students with high and low competence of writing skill employed comparable rates of discourse markers in their essays. Those who have lower competence of writing skill were found using more limited sets of discourse markers than those who have higher competence of writing skill. The students having low competence of writing skill were also found using these DMs in narrow range of functions and in a more limited set of positions. Moreover, the discourse markers that are used by the students having low competence of writing skill were found more redundant from the point of view of syntactic categories. On the other hand, the DMs used by the high competence of writing skill were found more varieties. It could be concluded that the use of discourse markers is affected by the levels of writing competence of EFL learners. Keywords: discourse markers, EFL learners, English language proficiency, written discourse.